Synthesis and Characterization of Barium Hexafluoridoosmates; Crystals; Vol. 8, iss. 1 - Ivlev S. I. Sergey Ivanovich; Karttunen A. J. Antti; Buchner M. R. Magnus; Ostvald R. V. Roman Vyacheslavovich; Kraus F. Florian (2018, 2018)
Title screen